2010
DOI: 10.4103/0974-777x.68538
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug resistant Acinetobacter

Abstract: Emergence and spread of Acinetobacter species, resistant to most of the available antimicrobial agents, is an area of great concern. It is now being frequently associated with healthcare associated infections. Literature was searched at PUBMED, Google Scholar, and Cochrane Library, using the terms ‘Acinetobacter Resistance, multidrug resistant (MDR), Antimicrobial Therapy, Outbreak, Colistin, Tigecycline, AmpC enzymes, and carbapenemases in various combinations. The terms such as MDR, Extensively Drug Resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
399
0
13

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 459 publications
(418 citation statements)
references
References 95 publications
(170 reference statements)
6
399
0
13
Order By: Relevance
“…The susceptibility tests were performed using Etest on Mueller-Hinton agar, and the results were evaluated using the CLSI breakpoints for microdilution methods (15). A strain resistant to at least three classes of antimicrobial agents-all penicillins and cephalosporins (including inhibitor combinations), fluoroquinolones, and aminoglycosides-was called multidrug resistant (MDR) (16). An MDR strain also resistant to imipenem was called extensively drug resistant (XDR) (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The susceptibility tests were performed using Etest on Mueller-Hinton agar, and the results were evaluated using the CLSI breakpoints for microdilution methods (15). A strain resistant to at least three classes of antimicrobial agents-all penicillins and cephalosporins (including inhibitor combinations), fluoroquinolones, and aminoglycosides-was called multidrug resistant (MDR) (16). An MDR strain also resistant to imipenem was called extensively drug resistant (XDR) (16).…”
mentioning
confidence: 99%
“…A strain resistant to at least three classes of antimicrobial agents-all penicillins and cephalosporins (including inhibitor combinations), fluoroquinolones, and aminoglycosides-was called multidrug resistant (MDR) (16). An MDR strain also resistant to imipenem was called extensively drug resistant (XDR) (16). All the outbreakassociated isolates were multidrug resistant (47 XDR and 7 MDR); in contrast, 67.6% of the non-outbreak-associated isolates were multidrug resistant (43 XDR and 3 MDR, out of 68 isolates), as shown in Fig.…”
mentioning
confidence: 99%
“…It is a virulent bacteria and very resistant to adverse conditions and is an emerging pathogen of nosocomial infections, particularly patients admitted in the ICU and on mechanical ventilation (Manchanda et al, 2010) (Table 1- (Babu et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The emergence of extended resistant Acinetobacter spp. was rapidly spreading to even newer antimicrobials and they acquired resistance faster than other Gram-negative organisms due to their ease of survival in the hospital environment, their immense potential to cause nosocomial outbreaks and their biofilm forming ability which played a crucial role in their in-vitro and in-vivo survival [20]. This study showed that ≥66% of A. bumannii isolates were resistant to almost all tested antibiotics and this clearly indicated how problematic to have patients infected with this organism and the minimal chances available to find proper treatment.…”
Section: Discussionmentioning
confidence: 99%